2020
DOI: 10.3389/fnins.2020.00469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleep Deprivation on the Working Memory-Related N2-P3 Components of the Event-Related Potential Waveform

Abstract: Working memory is very sensitive to acute sleep deprivation, and many studies focus on the brain areas or network activities of working memory after sleep deprivation. However, little is known about event-related potential (ERP)-related changes in working memory after sleep loss. The purpose of this research was to explore the effects of 36 h of total sleep deprivation (TSD) on working memory through ERPs. Sixteen healthy college students performed working memory tasks while rested and after 36 h of TSD, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 52 publications
6
22
2
1
Order By: Relevance
“…In the present study, we analyzed ERPs to investigate the effects of 8 h of RS on working memory impairments induced by 36 h of TSD. Our previous results revealed that TSD signi cantly impairs accuracy in 2-back working memory tasks [43]. The current behavioral ndings demonstrate that 8 h of RS can improve both accuracy and the number of correct responses per unit time in such tasks.…”
Section: Behavioral Performancesupporting
confidence: 64%
See 2 more Smart Citations
“…In the present study, we analyzed ERPs to investigate the effects of 8 h of RS on working memory impairments induced by 36 h of TSD. Our previous results revealed that TSD signi cantly impairs accuracy in 2-back working memory tasks [43]. The current behavioral ndings demonstrate that 8 h of RS can improve both accuracy and the number of correct responses per unit time in such tasks.…”
Section: Behavioral Performancesupporting
confidence: 64%
“…Although the present behavioral and EEG data support our hypothesis that 8 h of RS can attenuate impairments in working memory caused by 36 h of TSD, we did not observe signi cant changes in all indicators identi ed in our previous study [43]. Insu cient sleep may lead individuals to provide conservative estimates of their performance, which may increase the likelihood of compensatory behaviors and protect against the negative consequences of SD [33].…”
Section: Behavioral Performancecontrasting
confidence: 56%
See 1 more Smart Citation
“…For working memory tasks, the effects of repetitive partial sleep deprivation (PSD) and TSD are not related to the level of execution load, and the effects of PSD are observed to be small ( Lo et al, 2012 ). Although in this study we only selected spatial working memory tasks, sleep deprivation also reduces the quality of information storage in pronunciation working memory ( Zhang et al, 2019 ) and damages the performance of the entire working memory system ( Peng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that sleep loss endangers individual physical and mental health, such as by increasing the risk of cardiovascular disease and obesity ( St-Onge and Zuraikat, 2019 ; Yu et al, 2019 ). It can also lead to a decline in individual cognitive functions, such as attention, working memory, executive function, and emotional management ( Killgore, 2010 ; Tantawy et al, 2013 ; Xie et al, 2015 ; Lo et al, 2016 ; Krause et al, 2017 ; Cunningham et al, 2018 ; Peng et al, 2020 ), leading to serious traffic accidents. Additionally, studies have shown that lack of sleep can make individual’s neural representation ability unstable ( Poh and Chee, 2017 ).…”
Section: Introductionmentioning
confidence: 99%